Analysis of Peanut Farming Income in Lanne Village, Tondong Tallasa Subdistrict, Pangkajene and Islands Regency - Ahmad Reskullah; Andi Amran Asriadi; Andi Rahayu Anwar (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to determine the amount of production costs incurred by farmers and analyze the amount of income farmers earn from peanut farming in Lanne Village, Tondong Tallasa District, Pangkajene and Islands Regency. This study was conducted using the simple random sampling method. The research sample was taken randomly in Lanne Village. All peanut farmers who were members of the tanin group were included in the research population. The selection of farmer samples was carried out using a simple random sampling method, resulting in 165 farmers as samples, 24 of whom represented 15%. For data analysis, this study used quantitative descriptive analysis and calculated the analysis of costs, receipts, and income. The results showed that the costs incurred from peanut farming were fixed costs of IDR 3,812,333 and variable costs of IDR 3,020,208. Thus, the total cost of peanut farming was IDR 6,832,542. The revenue from peanut farming is IDR.88,032,466, and the income from peanut farming is IDR. 81,199,925 per planting season. This figure shows that the income obtained from peanut farming is very profitable.